2016
DOI: 10.1186/s40880-016-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic polymorphisms of the transporters organic cation transporter 2 (OCT2), multidrug and toxin extrusion 1 (MATE1), and ATP-binding cassette subfamily C member 2 (ABCC2) with platinum-based chemotherapy response and toxicity in non-small cell lung cancer patients

Abstract: BackgroundPlatinum-based chemotherapy is the first-line treatment of non-small cell lung cancer (NSCLC); it is therefore important to discover biomarkers that can be used to predict the efficacy and toxicity of this treatment. Four important transporter genes are expressed in the kidney, including organic cation transporter 2 (OCT2), multidrug and toxin extrusion 1 (MATE1), ATP-binding cassette subfamily B member 1 (ABCB1), and ATP-binding cassette subfamily C member 2 (ABCC2), and genetic polymorphisms in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…The presence of the SLC22A2 variant was associated with maintenance of serum creatinine. The SLC22A2 polymorphism rs316019 (G808T; Ser270Ala) has also been associated with protection from cisplatin ototoxicity [ 36 ], odds of hepatotoxicity and hematologic toxicity secondary to platinum chemotherapy [ 37 ], and increased metformin renal and secretory clearance [ 38 ]. In the current study, patients heterozygous vs. homozygous wildtype for the SLC22A2 rs316019 polymorphism had associated higher concentrations and fold-changes in urinary KIM-1 at baseline, Day 3, and Day 10 as compared to wildtype homozygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the SLC22A2 variant was associated with maintenance of serum creatinine. The SLC22A2 polymorphism rs316019 (G808T; Ser270Ala) has also been associated with protection from cisplatin ototoxicity [ 36 ], odds of hepatotoxicity and hematologic toxicity secondary to platinum chemotherapy [ 37 ], and increased metformin renal and secretory clearance [ 38 ]. In the current study, patients heterozygous vs. homozygous wildtype for the SLC22A2 rs316019 polymorphism had associated higher concentrations and fold-changes in urinary KIM-1 at baseline, Day 3, and Day 10 as compared to wildtype homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…The transporters MATE1 and MRP2 are brush border proteins that efflux cisplatin from proximal tubule cells to urine and reduce the susceptibility to nephrotoxicity [ 18 , 19 ]. A previous publication noted that the SLC47A1 rs2289669 variant was linked to hematological toxicity secondary to platinum containing chemotherapy [ 37 ]. Using oxaliplatin as a substrate, an in vitro study with SLC47A1 -transfected variants in HEK-293 cells demonstrated loss of MATE1 function [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the genetic basis in platinum‐based therapy is much complicated, in addition to DNA repair pathway, the process of influx, detoxification and apoptosis may also exert influences on the effect of platinum agents . Single DNA biomarker may exhibit a slight effect on the clinical outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies didn't find significant association between ABCB1 c.3435 C>T polymorphism and cisplatin toxicity [18,19,20]. Different genetic association results from different studies, may be explained by several factors such as the limited sample size of the patients included in the studies, heterogeneity of treatment protocols, treatment intent (curative vs palliative) and ethnicity.…”
Section: Discussionmentioning
confidence: 95%